Settlement Of Bad Loans Through Debt Payment Obligation Submitting Institutions (PKPU) - Dini Syakina Siregar (Journal of Law Science, 2021)
In order to enter the era of globalization and face the growth of the national economy, the banking sector is one sector that must be developed and utilized optimally. Especially through the provision of facilities provided by the banking sector for the community. The problem formulated in writing this thesis is how to handle bad loans in the banking environment, then discussed again What is the legal relationship between the Suspension of Debt Payment Obligations (PKPU) and bad loans, then discussed about How to settle bad loans through the Debt Payment Obligation Suspension Agency. (PKPU).The research that will be conducted is normative legal research. Normative research based on primary and secondary legal materials, namely the intarization of regulations relating to the writing of the author's thesis. The data collection technique was carried out by means of library research (library research). From the data that has been collected, both primary data and secondary data, then processed and analyzed using qualitative descriptive analysis techniques. Bad credit (Non Performing Loan / NPL) is where the credit cannot run as agreed in the credit contract agreement. Bad credit or credit failure can occur for many reasons. To avoid the occurrence of bad credit, it is necessary to control. Every loan disbursement of course has complied with banking regulations and is in accordance with sound credit principles. If indeed in the future, the credit develops into bad credit, then PKPU will be an alternative for the debtor and creditor in repaying the credit. As long as PKPU lasts, debtors cannot be forced to pay their debts. All execution actions that have been assessed to obtain debt repayment, must be suspended.